Comparative Study of Organic Parameters of Soils from Three Selected Universities in Port Harcourt Metropolis, Nigeria - Iyama, William Azuka; Edori, Onisogen Simeon (European Journal of Applied Sciences, 2021)
This research study was based on the comparative analysis of hydrocarbon content of soil samples from the 3-selected university campuses of Uniport, RSU and IAUE. Samples were collected from three different points to establish the composite samples within spaces of 500m apart as to obtain representative samples. The parameters for the determination of the hydrocarbon content were measured using the following methods, THC (ASTM D3921), PAHs (USEPA 8270D), TOG (ASTM D3921), TOC (Walkely-Black) and TOM (Walkely-Black). The hydrocarbon content analysis was done using THC (mg/kg), PAHs, TOG, TOC and TOM. The mean results of THC in soils of Uniport, RSU and IAUE were 6139± 146, 6075± 191, 6823± 337; PAHs were 16.36± 0.14, 16.43 ± 0.09 and 16.88± 0.23; for TOG were 10777±6.36, 10689±55.86, and 10839±50.20; for TOC (%) were 5.11±0.50, 4.75±0.25, and 3.33±0.76, whereas TOM recorded 8.81±0.86, 8.18±0.42 and 5.78± 1.28 respectively. The analysis of variance (ANOVA) showed that there was no significant difference in the soil hydrocarbon content for Uniport, RSU and IAUE mostly due to the similar soil structure, texture and geology but most importantly similar kinds of activities on campuses (p<0.05). These results are prompt indications of hydrocarbon pollution and hence adequate monitoring and control of deleterious anthropogenic inputs be put in place to sustain the already degraded soil.